2020
DOI: 10.30737/jatiunik.v3i2.842
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Single Exponential Smoothing (SES) dalam Perhitungan Jumlah Permintaan Air Mineral Pada PT. Akasha Wira International

Abstract: Daily needs that are priceless but useful for health one of which is mineral water. The need for mineral water increases with the high demand in the market. The purpose of this study was to determine the forecasting of the number of requests for 330 ml shortneck mineral water products in the future using the Single Exponential Smoothing (SES) method. Limitation of the problem is discussing the number of requests in the first half of 2020, the data used were obtained from PT. Akasha Wira International from Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
1
0
3
Order By: Relevance
“…Prediction of Flower Board Sales Using the Double Exponential Smoothing Method concluded that the resulting error percentage was 5.45% with parameter α = 0.5 for the forecast of flower board sales [9]. And in the previous study, entitled "IMPLEMENTATION OF SINGLE EXPONENTIAL SMOOTHING (SES) IN CALCULATION OF THE AMOUNT OF MINERAL WATER DEMAND" [10], concluded that in forecasting semester I of 2020 using the Single Exponential Smoothing (SES) method with α = 0.9 is 2,177,634 330 ml short neck mineral water unit. Meanwhile, the calculation of the Mean Absolute Deviation (MAD) α = 0.9 has a value of 1,860 error units that occur in forecasting demand data in the semester I of 2022.…”
Section: Preliminarymentioning
confidence: 98%
“…Prediction of Flower Board Sales Using the Double Exponential Smoothing Method concluded that the resulting error percentage was 5.45% with parameter α = 0.5 for the forecast of flower board sales [9]. And in the previous study, entitled "IMPLEMENTATION OF SINGLE EXPONENTIAL SMOOTHING (SES) IN CALCULATION OF THE AMOUNT OF MINERAL WATER DEMAND" [10], concluded that in forecasting semester I of 2020 using the Single Exponential Smoothing (SES) method with α = 0.9 is 2,177,634 330 ml short neck mineral water unit. Meanwhile, the calculation of the Mean Absolute Deviation (MAD) α = 0.9 has a value of 1,860 error units that occur in forecasting demand data in the semester I of 2022.…”
Section: Preliminarymentioning
confidence: 98%
“…Penelitian menggunakan metode Single Exponential Smoothing untuk prediksi telah banyak dilakukan, diantaranya: prediksi penjualan gamis [4], harga emas [5], penerimaan mahasiswa baru [6], peramalan penjualan barang [7], penjualan minuman kemasan [8], penjualan lensa kacamata [9], dan permintaan air mineral [10]. Bahkan pada salah satu penelitian tersebut, hasil akurasi yang dihitung menggunakan MAPE dengan nilai alpha 0,1 mencapai 2% [7].…”
Section: Pendahuluanunclassified
“…Manajemen persediaan adalah produk yang disimpan untuk memenuhi tujuan proses produksi maupun distribusi (Indrasari, 2020). Kegiatan utama yang dilakukan dalam manajemen persediaan untuk periode berjalan, memastikan persediaan dikelola dengan optimal, dan efisiensi dalam arti dapat memperkecil biaya persediaan (Ivanov et al, 2017).…”
Section: B Manajemen Persediaanunclassified